Long-Term Risks of Early Initiation of Breastfeeding to Mothers and Infants in Asia: a Systematic Review - Raisa Nurwany; Syifa Alkaf; Jeyaseelan, Ajay Varmaa (Andalas Obstetrics And Gynecology Journal, 2024)
Objective: This systematic review aims to determine the long-term risks of early initiation of breastfeeding in mothers and babies in Asia. Method: The method used in writing this literature review is systematization using keywords, namely "Early Initiation of Breastfeeding", "Breastfeeding", "ASI", "Asia", "Risk", "Baby and Mother", "Long Term Risk" , and "Benefits".A literature search was conducted using Google Scholar, Pubmed and NCBI databases. Results: From the results of a literature search based on keywords, 25 journals were obtained, of which seven journals met the criteria for long-term risk of IMD for mothers and babies in Asia. One study in this study used a systematic review, five studies used a retrospective cohort study, and one study used a cross-sectional study. The study found many positive risks and benefits of early initiation of breastfeeding for mothers and babies in the long term in Asia. Conclusion: Positive risks for babies include increasing immunity, reducing the risk of death, and preventing obesity. Meanwhile, long-term risks for mothers include accelerating uterine involution, preventing breast cancer, and reducing the risk of diabetes and prediabetes in mothers who have experienced gestational diabetes.